Decentring the 'places' of citizens in national curriculum: the Australian history curriculum. Issue 1 (2nd January 2019) - Halbert, Kelsey; Salter, Peta
Abstract: There is debate internationally about the production of curriculum texts and the epistemologies underpinning the knowledge legitimated in national curricula. National History curricula in particular are a source of contention bounded by calls for coherent and unifying national narratives that are inclusive and reflect the complexity of the discipline and historical consciousness of the nation to which they are bound. This paper uses critical spatial theory to highlight the 'spaces' and 'places' of the Australian Curriculum History (years 7–10) which organise and disorganise representations of identities in and out of the centre of the national narrative. Interrogating the impact of these representations within purported inclusive and cohesive national narratives draws attention to the notions of belonging presented to Australian citizens. We argue that resistance to normative national narratives and colonial legacies presented with place-based identities can reinhabit the curriculum. This reinhabiting and decentring seeks to engage History students with alternative perspectives and articulations to the national narrative, and foster meaningful connections to place and citizenship. Finally, critical place-based education approaches invite an embodied local/global citizen through local and marginalised knowledges.